THE ANALYSIS ILLOCUTIONARY ACTS OF USTADZ HANAN ATTAKI, LC ON VIDEO UST. HANAN ATTAKI YOUTUBE CHANNEL - Sholihah, Ajrina Al Mar'atus; Syahrizal, Trisnendri (IKIP Siliwangi, 2021)
The purpose of this study to analyze type of illocutionary speech acts that used by Hanan Attaki and identifying speech acts utterance by Hanan Attaki on Youtube. The method used in this study is the qualitative descriptive method because this is done only based on the fact and the writer describes the result in from words and the explanation of the result. Data collection method that used is scrutinized method and make a script, is scrutinize use of language by Ustadz Hanan Attaki, then the data is note and classified based on type of illocutionary. In this result the writer analyze all type of illucationary speech act used by Ustadz Hanan Attaki on Video Ust. Hanan Attaki Youtube Channel. The result of this study found 65 clauses that contain the type of illocutionary speech acts, there are representatives (37), directives (22), declarative (5) and commissive (1) each type of the speech acts are delivering different meaning and representative is the most widely used by Ustadz Hanan Attaki. It fits with the illocutionary speech act theory as religious speech containing factual matters raised by religious leaders. Keywords: Youtube, Pragmatics, Speech Acts, Illocutionary